Genome-wide association study identifies five new susceptibility loci for primary angle closure glaucoma - Khor, Chiea Chuen; Jonas, Jost B. (Nature genetics, 2016)
Primary angle closure glaucoma (PACG) is a major cause of blindness worldwide. We conducted a genome-wide association study (GWAS) followed by replication in a combined total of 10,503 PACG cases and 29,567 controls drawn from 24 countries across Asia, Australia, Europe, North America, and South America. We observed significant evidence of disease association at five new genetic loci upon meta-analysis of all patient collections. These loci are at EPDR1 rs3816415 (odds ratio (OR) = 1.24, P = 5.94 x 10-15), CHAT rs1258267 (OR = 1.22, P = 2.85 x 10-16), GLIS3 rs736893 (OR = 1.18, P = 1.43 x 10-14), FERMT2 rs7494379 (OR = 1.14, P = 3.43 x 10-11), and DPM2-FAM102A rs3739821 (OR = 1.15, P = 8.32 x 10-12). We also confirmed significant association at three previously described loci (P < 5 x 10-8 for each sentinel SNP at PLEKHA7, COL11A1, and PCMTD1-ST18)1, providing new insights into the biology of PACG.
Gesehen am 07.05.2019